Assessing Student’s Readiness For Working : A Soft Skill Perspective on School’s Led Internship Program - Mochamad Syaiful Mustofa; Cucuk Wawan Budiyanto; A G Tamrin (Journal of Informatics and Vocational Education, 2018)
This research aims to know the influence of the work practices of the industry (prakerin) or commonly called internships students on vocational schools computer network engineering programs skills by finding the answers to (1) the constraints being experienced in the implementation of the internship students, (2) efforts are being made to facilitate school students in the implementation of the internship, (3) industrial conditions that contribute to internship, (4) the role of apprenticeship in preparing students enter the workforce, (5) swept up from apprentice implementation against the ability the practice of students. This research uses the participant from the teacher as much as 5 participants, from the students as much as 9 participants and industry as much as 4 participants with random sampling. This research uses qualitative descriptive method of data collection in the form of interviews to answer problems and use of data triangulation analysis to analyze the results of the interview. Seeing the situation, researchers are trying to find answers to these problems to motivate students of vocational school that will run an internship with the show the benefits that will be able students in internships as a provision towards career after graduation the school. In this study researchers using qualitative descriptive method to find answers to problems that arise. Researchers found that the presence of an intern is expected to be more mature, preparing and ripen in dabbling in the world of industry and society by becoming a skilled workforce. have the competitiveness as well as the presence of team work in carrying out the work with a good and professional management. With the abilities, skills and attitude to work, not with just enough diploma. Soft skill into more value for students in post-graduate internship experience. So with the findings expected to be part of the motivation of students to perform an internship with a serious and useful benefit to reach working age.